Local Beliefs in Chinese Temples in West Java - Hartati, C. Dewi; Chandra, Yulie Neila; Wijayanti, Gustini (GoAcademica Research & Publishing, 2024)
This article writes about an overview of local beliefs in Chinese temples in West Java. Existing local beliefs can be in the form of worship of local sacred figures represented in various forms. This research is a qualitative research method with the aim of providing an in-depth description of local beliefs in Chinese temple in West Java. The research was conducted in five temples in Bogor, Cibarusah, Jonggol, Cikarang. Besides that, it also conducted in Jakarta. Data collection techniques were carried out by in-depth interviews, observation and participant observations. The results of the study show that Chinese beliefs are inclusive and undergo a transformation from China to the archipelago by adapting local beliefs in the area where a temple is located. The purpose of adapting these local beliefs is to respect local sacred figures.